Optimizing the axis ratio of elliptical PCM encasement for enhanced thermal performance in radiant floor heating systems - Zhenyu Wang; Weijun Gao; Jian Sun; Yanna Gao (Scientific Reports)
Abstract With the rapid development of low-carbon buildings and energy-saving technologies, phase change materials (PCM) have been extensively applied in building floor heating systems due to their excellent thermal energy storage and temperature control characteristics. However, traditional encased PCM radiant floor heating systems (RFHS) exhibit drawbacks including slow thermal response, low thermal efficiency, and excessive structural layer thickness. This study proposes an innovative solution through CFD numerical simulation: replacing the conventional circular encasement with an elliptical encasement and optimizing the elliptical axis ratio to enhance the system’s thermal performance and reduce mortar layer thickness, thereby lowering construction costs. The study analyzes the thermal state of PCMs, temperature variations of the floor structure, and heat flux distribution. The results show that as the short axis (a) length of the elliptical encasement decreases, the floor’s thermal response becomes faster. When a = 1.5 times the radius of the hot water pipe, the floor achieves the optimal balance between thermal comfort and energy efficiency. Compared to the traditional design, this approach not only enhances thermal response speed and reduces energy consumption but also decreases the mortar layer thickness by 16.7%. This study provides a theoretical basis for optimizing RFHS integrated with PCMs and holds significant potential for engineering applications.